Noise Causes Work Stress in Traditional Boat Workers - Faiza, Sabrina Nurul; Febriyanto, Kresna (Universitas Airlangga, 2023)
Introduction: Noise is an unwelcome sound that disrupts workers. Noise is present in every workplace, including ship engine noise. Continuous noise exposure can result in health issues, including hearing loss. Noise can cause stress on traditional boat workers because being continuously exposed to noise causes an uncomfortable feeling in the work environment. This uncomfortable feeling can trigger stress on ferry boat workers. This study aims to determine the relationship between noise and work stress on ferry boat workers at the Pier of Kampung Baru Tengah, Balikpapan. Methods: This study used a quantitative approach with a cross-sectional research design with 44 respondents. The instruments used a Sound Level Meter to measure Noise Level and Dass 21 Questionnaire with an interview method to measure Job Stress. Results: As many as 35 respondents were exposed to noise caused by traditional boat engines, and more than 50% of workers did not experience work stress (normal). The results of this study indicated a relationship between noise and work stress in traditional boat workers. Conclusion: The direction of the association between noise and work stress was positive but low, meaning that, as noise levels rise, so does the risk of workplace stress.